Learning and staged equity financing - Blomkvist, Magnus; Korkeamäki, Timo; Takalo, Tuomas (Journal of Corporate Finance, 2022)
We propose a rationale for why firms often return to the equity market shortly after their initial public offering (IPO). We argue that hard to value firms conduct smaller IPOs, and that they return to the equity market conditional on a positive valuation signal. This is driven by two-way learning, as market information complements both corporate disclosure and internal information available to management. In contrast to prior studies, we find that information asymmetry is not a necessary condition for staged financing. Our arguments receive support in a sample of 3625 U.S. IPOs between 1980 and 2018.